2013
DOI: 10.1155/2013/643287
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphological Studies on the Prostate Gland of Donkey Equus Asinus during Different Seasons

Abstract: The objective of this study is to describe the histological and histochemical structures of the prostate gland during different seasons of the year. The experiment was carried out on the prostate gland of 24 sexually mature apparently healthy male donkeys (5 to 7 years) distributed over the four seasons of the year. The prostate gland was enveloped externally by a thick fibromuscular capsule. Fibromuscular septa arose from the deep aspect of the capsule dividing the prostate into variable numbers of lobules of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
11
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 32 publications
3
11
1
Order By: Relevance
“…The basal cells found at the base of the epithelium of the gland in E. helvum may be the source of cells for the regeneration. A similar occurrence was reported in the prostate gland of donkeys during the non‐breeding season (Abou‐Elhamd, Salem, & Selim, 2013) and in the prostate gland of rats after administration of cadmium (Chandler, Timms, Morton, & Groom, 1976). The apical membrane demarcations indicates apocrine mode of secretion in the bulbourethral gland of E. helvum during the dry season.…”
Section: Discussionsupporting
confidence: 77%
“…The basal cells found at the base of the epithelium of the gland in E. helvum may be the source of cells for the regeneration. A similar occurrence was reported in the prostate gland of donkeys during the non‐breeding season (Abou‐Elhamd, Salem, & Selim, 2013) and in the prostate gland of rats after administration of cadmium (Chandler, Timms, Morton, & Groom, 1976). The apical membrane demarcations indicates apocrine mode of secretion in the bulbourethral gland of E. helvum during the dry season.…”
Section: Discussionsupporting
confidence: 77%
“…Abou‐Elhamd et al. (2014) reported that the prostate gland of donkeys was active all over the year, but this activity was more pronounced during spring; the height of the glandular epithelium of the secretory end pieces of the prostate reached its maximal value in spring (14.67 ± 0.14 μm) by histological observations, but the interstitial connective tissue/glandular tissue ratio was the lowest level. In our study, there was no statistically significant difference in the thickness of the prostate lobe measured by ultrasound among spring, summer and autumn.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the studies have been reported on the enzyme histochemistry of accessory sex glands during different seasons in Gaddi Goat and Gaddi Sheep (Suri et al 2012) and donkey (Elhamd et al 2013), age related variation in buffalo (Sudhakar, 1982, Chopra, 1998, Anurag, 2000, Bangladeshi bull (Rahman et al 2010), ram (Roy et al1987, Selvinjose et al2009, and boar (Nagasailaja et al 2016). But the histoenzymic variation in buffalo accessory sex glands during different seasons sare still lacking, so the present investigation was carried out to study the distribution pattern of phosphatases, oxidoreductases and estrases with its functional activity in summer and winter seasons.…”
Section: Introductionmentioning
confidence: 99%